Melodies of Self-Love on Selena Gomez’s Songs: A Semiotic Analysis - Widhayanti, Wahyu Rosyita; Amalia, Syahara Dina (Journal of English Language and Education, 2025)
This research examined the depiction of self-love in Selena Gomez's music through the lens of Roland Barthes' Semiotic analysis model. A qualitative descriptive research was executed to analyse four songs namely: "Who Says," "I Won’t Apologise,"  "Lose You to Love Me," and "Rare" to figure out the self-love traits found in the four songs and to reveal their denotative and connotative implications in the lyrics from Semiotic perspective. The data were collected by textual analysis of the song lyrics using thematic categorization and analyzed using Barthes’ framework. From the eleven characteristics of self-love adopted from many scholars, the researchers found three essential traits of self-love, such as self-awareness, self-acceptance, and emotional resilience. Furthermore, the Semiotic analysis of Selena Gomez’s songs showed that "I Won’t Apologize" contains the most self-love themes, followed by "Lose You to Love Me," "Who Says," and "Rare." Each song highlights different aspects of self-love, from self-empowerment and emotional healing to self-worth and individuality. Using both literal and symbolic language, Gomez’s lyrics encourage resilience, self-acceptance, and personal growth while also challenging societal beauty standards and promoting emotional freedom.